The Faber book of northern folk-tales - Crossley-Holland, Kevin; Howard, Alan. (London : Faber and Faber, 1980)
Thirty-five folk tales from Scandinavia, Iceland, Germany, Flanders, and the British Isles.
Companion vol. to the Faber book of northern legends.
Bibliography: p. [155]-157.
Keywords: Tales; Folklore